ANALISIS FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP RESIKO SISTEMATIK (BETA SAHAM) PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2012-2015 - Dina Setyawati, 12.05.52.0187; Suwarti, Titiek (Students Journal of Accounting and Banking, 2017)
This study aims to transform and analyze the effect of financial leverage, company size, profitability, inflation, interest rates and the exchange rate against the systematic risk in mining companies listed on the Indonesian Stock Exchange for the period 2012-2015. In this study, researchers used a population of financial data mining company listed on the Stock Exchange during the years 2012-2015. The method used is purposive sampling method. Test equipment in this study using multiple linear regression, partial test (t test) and f simultaneous test (test f). The results of this study are positive effect on the financial laverage, company size, and inflation systematic risks. While Interest rates, profitability and the exchange rate has no effect on the systematic risk.Keywords:Â Financial Leverage, Company Size, Profitability, Inflation, Interest Rates, Exchange Rates, The Systematic Risk